2022
DOI: 10.1111/jfpp.16493
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of essential and toxic elements from pepper in different ripening stages using Box–Behnken design

Abstract: The influence of extraction parameters on the ultrasonically assisted extraction (UAE) of K, Na, Ca, Mg, Zn, Cu, Fe, Mn, Cr, Se, Mo, Li, Al, B, Pb, Hg, Cd, As, and Ni was studied to determine the conditions when a minimum of essential and maximum of toxic elements is leached from peppers, depending on its ripening stage. The effect of process variables was investigated by using Box–Behnken design. Each essential element had a different optimal condition for minimal leaching, while the toxic elements were predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…BBD is a three‐level design frequently used in response surface methodology (RSM) optimization (Lučić et al, 2022; Shrivastava & Daharwal, 2022). It fits a second‐order regression model (quadratic model) with fewer design points than central composite and other RSM designs with the same number of variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BBD is a three‐level design frequently used in response surface methodology (RSM) optimization (Lučić et al, 2022; Shrivastava & Daharwal, 2022). It fits a second‐order regression model (quadratic model) with fewer design points than central composite and other RSM designs with the same number of variables.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas t ex had a small influence on the DLLME process, t centr affected the process significantly.In addition to t centr , ANOVA revealed that V disp and NaCl were significant variables. Therefore, these three most influential variables were used as input to the second step of DLLME optimization, in which the Box-Behnken design (BBD) was applied.BBD is a three-level design frequently used in response surface methodology (RSM) optimization(Luči c et al, 2022;Shrivastava & Daharwal, 2022). It fits a second-order regression model (quadratic model) with fewer design points than central composite and other RSM designs with the same number of variables.…”
mentioning
confidence: 99%
“…Experimental design allows the study of the influence of several factors simultaneously [ 24 ]. Three graphs were used to interpret obtained results: Pareto chart, main effect plot, and interaction plot.…”
Section: Methodsmentioning
confidence: 99%